2017
DOI: 10.1371/journal.pone.0178783
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of caspofungin acetate to guide optimal dosing in cats

Abstract: Cats are the most common mammal to develop invasive fungal rhinosinusitis caused by cryptic species in Aspergillus section Fumigati that are resistant to azoles but susceptible to caspofungin. In this study nonlinear mixed-effects pharmacokinetic modeling and simulation was used to investigate caspofungin pharmacokinetics and explore dosing regimens in cats using caspofungin minimum effective concentrations (MECs). Plasma concentrations in healthy cats were determined using HPLC-MS/MS after administration of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Caspofungin is the only echinocandin for which pharmacokinetic data are available in cats. 60 < Activity Echinocandins are fungicidal against Candida species, and fungistatic against Aspergillus, Penicillium and Purpureocillium species. 61 They have some activity against Sporothrix, Bipolaris, Scedosporium, Pseud allescheria and Fonsecaea species.…”
Section: Echinocandinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Caspofungin is the only echinocandin for which pharmacokinetic data are available in cats. 60 < Activity Echinocandins are fungicidal against Candida species, and fungistatic against Aspergillus, Penicillium and Purpureocillium species. 61 They have some activity against Sporothrix, Bipolaris, Scedosporium, Pseud allescheria and Fonsecaea species.…”
Section: Echinocandinsmentioning
confidence: 99%
“…68 A pharmacokinetic study, in which caspofungin was administered to six cats for 7 days, reported transient fever in one cat and transient diarrhoea in another as the only AEs. 60 < Clinical use Caspofungin has been used to treat SoA in cats.…”
Section: Caspofunginmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 • Determining the pharmacokinetics and pharmacodynamics of caspofungin in healthy cats, formed the basis of a Master's thesis and resulted in a presentation at an international conference and a publication. 7 This work was just one part of 6 years of research on canine and feline aspergillosis, with four prior publications from previous ACAHF funding.…”
Section: Hr Specialistmentioning
confidence: 99%